Analisis Penerapan Kuota Gender Kandidat Perempuan Partai Keadilan Sejahtera Pada Pemilihan Umum Legislatif 2024 - Gunawan, Wahyu; Nurdin, Nurdin (Jurnal Ilmiah Global Education, 2025)
This study aims to discuss the perspective of the Prosperous Justice Party in maximizing the 30% gender quota for female candidates in all electoral districts in the 2024 legislative elections. The purpose of the study is to analyze the political phenomenon of the Prosperous Justice Party which is the only political party among 18 (eighteen) political parties that can fulfill the 30% quota for female legislative candidates in all electoral districts in the 2024 legislative elections. This study uses a qualitative approach with a descriptive research type. Data collection is sourced from primary data through in-depth interviews with several informants. While secondary data comes from literature studies, both relevant books and articles, documentation in the form of laws and regulations related to legislative elections. In answering the research problems, the researcher uses the theory of gender quotas for female candidates and the concept of women's representation in parliament. The results of the study show that the Prosperous Justice Party has succeeded in implementing a gender quota of 30% for female candidates in the 2024 Legislative Elections as mandated by Law Number 7 of 2017 concerning Elections, Article 245. The success of the Prosperous Justice Party is in line with the party's motivation to be more female-friendly, both through work programs, female cadre formation to fill strategic positions within the party, and open institutionalization of female cadres as party elites.